2021
DOI: 10.3390/metabo11110742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n-3 (Omega-3) Polyunsaturated Fatty Acid Supplementation on Metabolic and Inflammatory Biomarkers and Body Weight in Patients with Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis of RCTs

Abstract: Beneficial effects of n-3 fatty acids on metabolic biomarkers in patients with type 2 diabetes (T2DM) has been reported. The objectives of this current research were to investigate the effects of n-3 supplementation on metabolic factors, weight, and body mass index (BMI) in patients with type 2 diabetes mellitus (T2DM), using a meta-analysis of randomized, controlled trials (RCTs). Online databases PubMed, Embase, Web of Science, and Science Direct were searched until 2021 to identify eligible articles. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Fish oil and ALA have also been shown to exhibit anti-inflammatory effects [23][24][25]. Although the meta-analysis indicated that the reduction in the c-reactive protein were not statistically significant [20,26]. The reduction of IL-6 after EPA and DHA supplementation was significant in T2DM patients [27].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Fish oil and ALA have also been shown to exhibit anti-inflammatory effects [23][24][25]. Although the meta-analysis indicated that the reduction in the c-reactive protein were not statistically significant [20,26]. The reduction of IL-6 after EPA and DHA supplementation was significant in T2DM patients [27].…”
Section: Discussionmentioning
confidence: 98%
“…Many meta-analyses showed that EPA and DHA consumption can significantly reduce the levels of TG, LDL in T2DM patients [5,19]. And n-3 PUFA intake for both ≤8 and > 8 weeks could significantly increase the HDL level [20]. It is well established that T2DM is associated with dyslipidemia and that EPA and DHA supplementation has long been indicated in the treatment of hyperlipidemia in T2DM and pre-diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings revealed that ω-3 PUFA doses >1 g/d significantly changed LDL and HDL levels. However, the statistically significant reduction in LDL concentration occurred only when ω-3 PUFAs were consumed for more than 8 weeks, while improvement in HDL level was noticed during all analyzed periods [41 ▪ ]. A previous meta-analysis of 45 RCTs, involving 2647 patients with T2DM, showed an association between ω-3 PUFA supplementation and favorable improvement in lipid profile, inflammatory markers and HbA1c level [42].…”
Section: Latest Clinical Trials and Meta-analysis Of Trials Related T...mentioning
confidence: 91%